Elucidation of cold adaptation in Glaciimonas sp. PAMC28666 with special focus on trehalose biosynthesis - Shrestha, Prasansah; Karmacharya, Jayram; Han, So-Ra; Lee, Jun Hyuck; Oh, Tae-Jin (Frontiers in Microbiology, 2023)
Glaciimonas sp. PAMC28666, an extremophilic bacterium thriving in Antarctic soil and belonging to the Oxalobacteraceae family, represents the only complete genome of its genus available in the NCBI database. Its genome measures 5.2 Mb and comprises 4,476 genes (4,350 protein-coding and 72 non-coding). Phylogenetic analysis shows the strain PAMC28666 in a unique branch within the genus Glaciimonas, closely related to Glaciimonas alpine Cr9-12, supported by robust bootstrap values. In addition, strain PAMC28666 showed 77.08 and 23.3% ANI and DDH, respectively, with Glaciimonas sp. PCH181.This study focuses on how polar strain PAMC28666 responds to freeze–thaw conditions, Experimental results revealed a notable survival rate of 47.28% when subjected to a temperature of 15°C for a period of 10 days. Notably, two genes known to be responsive to cold stress, Trehalose 6-phosphate synthase (otsA) and Trehalose 6-phosphate phosphatase (otsB), exhibited increased expression levels as the temperature shifted from 25°C to 15°C. The upregulation of otsAB and the consequent synthesis of trehalose play pivotal roles in enhancing the cold resistance of strain PAMC28666, offering valuable insights into the correlation between trehalose production and adaptation to cold stress. Furthermore, research into this neglected cold-adapted variation, like Glaciimonas sp. PAMC28666, has the potential to shed light on how trehalose is produced in cold-adapted environments Additionally, there is potential to extract trehalose compounds from this strain for diverse biotechnological applications, including food and cosmetics, with ongoing research exploring its unique properties.